A variação das vogais médias pretônicas no português de Brasília: um fenômeno neogramático ou de difusão lexical? (Revista de Estudos da Linguagem, 1992)
This study addresses a controversial issue of the implementation of the raising role oflhe pretonic vowels/el and/ol in Brazilian Portuguese. The phenomenon has been traditionally regarded as a case of vowel harmony. A strong influence ofanalogical processes affecting derived words has also been pointed out. More recent studies have suggested however lhat the role is lexically implemented. The data for lhe present study come from the contemporary Portuguese spoken by informants from Brasília, and from Ola Portuguese and lhe Galician. The quantitative analysis of lhe synchronic data has partially confirmed the two conditioning hypotheses that are couched within lhe Neogrammarian view of lhe phenomenon. The alphabetical ordering of lhe tokens however has revealed a residue of words in which lhe variation can only be taken into account by the Lexical Diffusion model of role implementation. The qualitative analysis oflhe diachronic data has accordingly shown that in lhe process of evolution from Latin into Modem Portuguese words with pretonic leI and/o! have followed two' different tracks lhat can neither be explained by phonological conditioning nor by analogy: in some groups of words lhe pretonic vowel evolved into a categorical high or a categorical mid vowel, whereas in olher groups the realization of the pretonic vowels has never become categorical.